Increasing life-space mobility in community-dwelling older persons with cognitive impairment following rehabilitation: a randomized controlled trial - Ullrich, Phoebe; Werner, Christian; Bongartz, Martin; Eckert, Tobias; Abel, Bastian; Schönstein, Anton; Kiss, Rainer; Hauer, Klaus (The journals of gerontology. Series A, Biological sciences, medical sciences, 2021)
Community-dwelling older persons with cognitive impairment (CI) following discharge from geriatric rehabilitation are at high risk of losing life-space mobility (LSM). Interventions to improve their LSM are, however, still lacking. The aim of this study was to evaluate the effects of a CI-specific, home-based physical training and activity promotion program on LSM.Older persons with mild-to-moderate CI (Mini-Mental State Examination: 17-26 points) discharged home from rehabilitation were included in this double-blinded, randomized, placebo-controlled trial with a 12-week intervention period and 12-week follow-up period. The intervention group received a CI-specific, home-based strength, balance, and walking training supported by tailored motivational strategies. The control group received a placebo activity. LSM was evaluated by the Life-Space Assessment in Persons with Cognitive Impairment, including a composite score for LSM and 3 subscores for maximal, equipment-assisted, and independent life space. Mixed-model repeated-measures analyses were used.One hundred eighteen participants (82.3 ± 6.0 years) with CI (Mini-Mental State Examination: 23.3 ± 2.4) were randomized. After the intervention, the home-based training program resulted in a significant benefit in the Life-Space Assessment in Persons with Cognitive Impairment composite scores (b = 8.15; 95% confidence interval: 2.89-13.41; p = .003) and independent life-space subscores (b = 0.39; 95% confidence interval: 0.00-0.78; p = .048) in the intervention group (n = 63) compared to control group (n = 55). Other subscores and follow-up results were not significantly different.The home-based training program improved LSM and independent life space significantly in this vulnerable population. Effects were not sustained over the follow-up. The program may represent a model for improved transition from rehabilitation to the community to prevent high risk of LSM restriction.
Published: 06 October 2020
Gesehen am 03.12.2021